The terrain effect in vertical deflection in the northwest and highlands mountainous areas - Hoa, Pham Thi (Vietnam Journal of Earth Sciences, 2012)
This article presents the methods determining terrain effect in vertical deflection and the surveying result in the mountainous areas of the Northwest and Gia Lai-Kon Tum highlands. Based on the analysis and assessment of the calculations, the terrain effects invertical deflection, in the surveyed areas, occur with positive and negative value, complex variable. The terrain effect in vertical deflection is considerable (values of 30” and 14” for North West and highlands mountainous areas, respectively). Thus, it is necessary to ensure the highly detailed and accurate vertical deflection. Especially, the terrain effects in vertical deflection possess no linear relation with the topographic altitude at the surveying points. Thus, it can not calculate by simple method (only using height value of calculating point). It is necessary to calculate carefully by numerical integral or Spline linear function method with considerable radius of integral areas (about 50-60km).